The model of gas pool formation in Frakulla area, Albania - KOCI, R.; GJIKA, A.; AVDULAJ, Q.; KOCI, S. (Bulletin of the Geological Society of Greece, 2001)
Frakulla diapir is one of the studied diapirs in Albania. It is located in the western part of Albania. The Serravallian to Pliocene sediments belongs to the uppermost part of the Adriatic Basin, which is included in the central Mediterranean Basins group. Some anticline and syncline structures are indicated in the western part of Albania. These structures are placed in a linear way forming some structural ranges with SSE-NNW axis direction. Frakulla is one of these structures as a part of Vlora-Panaja-Frakkull range (Fig. 1). Based on the surface geology, well data and the interpretation of the seismic sections results that this structure is formed as a consequence of the mud diapir growth. This diapir is complicated with tectonic faults in both western and eastern flanks, which dip with angle 45-90° The southern and northern ends of the structure are clearly seen in the seismic sections and a number of wells penetrated these ends. We think that the Frakulla structure is a typical mud diapir surrounding in all directions by many gas sandstone beds. These sandstones are formed in a deltaic environment during the Messinian (Globorotalia conomiozea zone). Some factors affected the quantity of hydrocarbon accumulation are discussed in this paper like: structural character of the area, pattern and complexity of faulting around and over the mud diapir, depositional environment, rate of growth of the diapir and time of uplift. We think that the presence of gas accumulation in Frakulla area is as a consequence of a favorable interrelation of these factors